Electricity Consumption, Government Expenditure and Sustainable Development in Nigeria: A Co-integration Approach - Matthew, Oluwatoyin A.; Miebaka-Ogan, Tamunotonye; Popoola, Olabisi; Olawande, Tomike; Osabohien, Romanus; Urhie, Ese; Adediran, Oluwasogo; Ogunbiyi, Toun (International Journal of Energy Economics and Policy, 2019)
The government incurs both capital and recurrent expenditures so as to bring about the development of the Nigerian economy. Coupled with this is the fact that electricity power plays an important role in ensuring that aggregate output increases and the welfare of the people is affected positively. This study sets out to examine the long run relationship between electricity consumption, government expenditure and sustainable development in Nigeria employing the Johansen co-integration, Vector Error Correction Mechanism (VECM) and Granger causality estimation techniques. Secondary data were obtained from Central Bank of Nigeria Statistical Bulletin, United Nations Conference on Trade and Development (UNCTAD) and World Development Indicators (WDI) from 1980 to 2017. The results obtained from the study showed that government recurrent expenditure, gross fixed capital formation have a positive and significant relationship with GDP per capita in the long run. However, electricity consumption, government capital expenditure and total labour force had a negative but significant effect on GDP per capita in the long run. Hence, this study recommended that the government and relevant agencies should ensure that projects undertaken are profitable and people oriented. Also, strategies to improve electricity supply, government expenditure on capital and labour productivity should be encouraged. Keywords: Capital and Recurrent Expenditure, Electricity Consumption, Sustainable Development JEL Classifications: F61, I15, I25, L92 DOI: https://doi.org/10.32479/ijeep.7547